Noble Gas Data from recent ice in Antarctica for 86Kr problem - Severinghaus, Jeffrey; Shackleton, Sarah (IEDA: US Antarctic Program Data Center, 2019)
Abstract: This data comprises a survey of Recent ice from multiple sites in Antarctica using shallow ice cores to examine noble gas values in ice that nominally has the same Mean Ocean Temperature as today. The goal is to elucidate fractionation that occurs in the firn before air is trapped in bubbles in the ice, by making the assumption that the atmosphere noble gas content has not changed since this air was trappped. The ages of the air samples are typically early Industrial Revolution or late Holocene.